Intellectual capital investment and firm performance of the malaysian energy sector: A New perspective from a nonlinearity test - Asif, Jawad; Irene, Wei Kiong Ting; Qian, Long Kweh (Asia-Pacific Applied Economics Association, 2020)
This study examines the association between intellectual capital investment and firm performance of the Malaysian energy sector. A non-linear relationship between intellectual capital investment and firm performance is established. At low levels of intellectual capital investment, increasing investments in intellectual capital improve firm performance. After a cut-off point, increments to intellectual capital investment reduce firm performance.